Chimney Rock and the Ontology of Skyscapes: How Astronomy, Trade, and Pilgrimage Transformed Chimney Rock - McKim Malville, J (Journal of Skyscape Archaeology, 2015)
Because of its architectural style and excellent masonry, the Great House of Chimney Rock in southwestern Colorado has been identified as one of some 225 outliers of the Chaco Regional System. Located just below the spectacular double rock towers, the Great House is set in a dramatic and unique skyscape containing a number of sight-lines to extremes of the Sun and Moon. Once considered important as a calendrical station, which communicated astronomical information southward to Chaco Canyon, the Great House may have been primarily important as a place for viewing the juxtaposition of the gods of earth and sky, a theophany similar to that of dar?an of India. This paper proposes that the initial identification of a number of skyscapes as horizon calendars and calendrical stations should be reconsidered in the perspective of animism and alternate ontologies. Construction of the Great House may have been initiated by the local community and accomplished with the help of masons from its closest neighbour the Great House of Salmon. The area appears to have become a pilgrimage centre in its own right, not under hegemonic control of the powerful elites of Chaco Canyon. Rejection of the Chacoan influence is indicated by the construction by the local community of a structure that restricted entry to the area of the Great House. The decline of Chimney Rock as a pilgrimage centre sometime after 1093 AD was accompanied by the abandonment of the Salmon Great House, the breakup up of a trade network, and out-migration to the Taos Pueblo.